2021
DOI: 10.1080/21655979.2021.1943110
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological mechanism of mylabris in the treatment of leukemia based on bioinformatics and systematic pharmacology

Abstract: Leukemia is a common blood cancer, whose treatment usually necessitates chemo/radiotherapy and bone marrow transplant. Hence, safer and more effective options are urgently needed. Mylabris, the dried body of blister beetles, has been used extensively in traditional Chinese medicine. This study applied bioinformatics and systematic pharmacology to investigate the mechanism of action of mylabris in the treatment of leukemia. Five effective components and 35 corresponding target proteins were identified by screen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…The lack of selectivity in most cancer chemotherapy drugs and their primary side effect of inhibiting bone marrow hematopoietic stem cells results in MAC [ 25 ]. In this study, cyclophosphamide, commonly used in clinical settings, was employed to construct a MAC animal model.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of selectivity in most cancer chemotherapy drugs and their primary side effect of inhibiting bone marrow hematopoietic stem cells results in MAC [ 25 ]. In this study, cyclophosphamide, commonly used in clinical settings, was employed to construct a MAC animal model.…”
Section: Discussionmentioning
confidence: 99%
“…Recent advances in clinical research have shed more light on the potential of Chinese herbal medicines and their extracts for the treatment of leukemia. [ 39 ] Pharmacological studies have revealed that PHEB is widely used in clinical settings for the treatment of leukemia. [ 40 ] PHEB contains compounds that inhibit the growth of tumor cells in APL, a rare but highly curable form of leukemia.…”
Section: Discussionmentioning
confidence: 99%
“…This was further confirmed by the elevated p53 expression seen in the cochlea of Rest cKO mice. The endogenous p53 pathway, induced by stresses such as acute DNA damage, plays a critical role in apoptosis, cell growth and senescence [ 35 37 ]. p53 induces cell apoptosis through different methods, inducing the self-cleavage and activation of downstream caspase-3 [ 38 ].…”
Section: Discussionmentioning
confidence: 99%